The crystal structure of guinea pig 11beta-hydroxysteroid dehydrogenase type 1 provides a model for enzyme-lipid bilayer interactions. - Ogg, D; Elleby, B; Norström, C; Stefansson, K; Abrahmsén, L; Oppermann, U; Svensson, S (2005)
The metabolic reduction of 11-keto groups in glucocorticoid steroids such as cortisone leads to the nuclear receptor ligand cortisol. This conversion is an example of pre-receptor regulation and constitutes a novel pharmacological target for the treatment of metabolic disorders such as insulin resistance and possibly other derangements observed in the metabolic syndrome, such as hyperlipidemia, hypertension, and lowered insulin secretion. This reaction is carried out by the NADPH-dependent type 1 11beta-hydroxysteroid dehydrogenase (11beta-HSD1), an enzyme attached through an integral N-terminal transmembrane helix to the lipid bilayer and located with its active site within the lumen of the endoplasmic reticulum. Here we report the crystal structure of recombinant guinea pig 11beta-HSD1. This variant was determined in complex with NADP at 2.5 A resolution and crystallized in the presence of detergent and guanidinium hydrochloride. The overall structure of guinea pig 11beta-HSD1 shows a clear relationship to other members of the superfamily of short-chain dehydrogenases/reductases but harbors a unique C-terminal helical segment that fulfills three essential functions and accordingly is involved in subunit interactions, contributes to active site architecture, and is necessary for lipid-membrane interactions. The structure provides a model for enzyme-lipid bilayer interactions and suggests a funneling of lipophilic substrates such as steroid hormones from the hydrophobic membrane environment to the enzyme active site.